PENGENALAN TEKNOLOGI PRODUKSI KACANG TANAH SANGRAI UNTUK INDUSTRI RUMAH TANGGA DI DESA UWEN PANTAI, KECAMATAN TANIWEL TIMUR, SERAM BAGIAN BARAT - Nelson Gaspersz; Priska Marisa Pattiasina; Shielda Natalia Joris (PAKEM: Jurnal Pengabdian Kepada Masyarakat, 2026)
Maluku possesses substantial agricultural potential, particularly in peanut cultivation, which is extensively practiced in Uwen Pantai Village, East Taniwel Sub-district, West Seram Regency. Groundnut cultivation thrives due to favorable land conditions, minimal maintenance requirements, and relatively short harvest cycles of 3–4 months. The competitive market price positions peanuts as a promising commodity for enhancing community welfare. However, current peanut production and marketing practices remain predominantly traditional, operating at limited scales without adherence to market standards. This community empowerment program aims to enhance local capacity in roasted peanut processing through the introduction of modified rotating sand roaster technology. Employing a transformative learning approach, community members receive comprehensive training in technology application and market-oriented business management. The modified rotating sand roaster features innovative blunt blades positioned strategically within the sample tube to facilitate uniform heat distribution, ensuring consistent product quality with distinctive roasted flavor and aroma. The program encompasses socialization activities, participatory training, technology application, and continuous mentoring in production, packaging, and marketing. Initial implementation results demonstrate significant improvements: production capacity increased from small batches to 5–10 kg per cycle (2–3 hours), product packaging advanced from plain plastic to full-color labeled aluminum foil, and profit margins reached 84.48%. This initiative is expected to improve product quality and competitiveness, expand market access, facilitate business legalization, and ultimately contribute to post-pandemic economic recovery in Uwen Pantai Village.Abstract A maximum of 250 Indonesian words printed in italics with Cambria 10 point. The abstract should be clear, descriptive and should provide a brief overview of community service issues undertaken / researched. Abstracts include reasons for the selection of topics or the importance of research topics / community service, methods of research / devotion and outcome summary. The abstract should end with a comment about the importance of the result or a brief conclusion.